Gross and histomorphological effects of antiarthritic drug in experimental acute traumatic arthritis in donkeys - SINGH, K I; SOBTI, V K; ROY, K S (The Indian Journal of Animal Sciences, 2013)
Acute aseptic arthritis was induced in 8 healthy donkeys aged 3-4 years and weighing 80-100 kg. The animals were randomly divided into 2 groups A and B of 4 animals each. Group A served as a control whereas in group B antiarthritic drug (AD) was administered orally @ 20 g from day 2 to 26. In AD treated animals, the gross changes in the joint capsule. synovial membrane and articular cartilage were far less than those in control. Microscopically joint capsule showed complete longing of the intima layer and subintimal layer showed severe inflammatory reaction or even complete necrosis of the intima layer and fibrous capsule and synovial membrane in untreated animals. In AD-treated animals various layers of joint capsule showed organization and proliferation and inflammatory cells were not traceable. Synovial membrane of untreated animals showed less of alcinophilic material and was more PAS-positive as compared to treated animals. Calcium cartilage deposition was not evident in joint capsule of the treatment group. Degeneration of articular was observed microscopically in control group animals as marked by fibrillation and desquamation of pericohndrial tissue with different layers or even complete sloughing of the articular cartilage. Severity of articular cartilage changes in AD-treated animals was very much less than that in control group and the changes were restricted to tangential layer only.